Perancangan Pertanyaan Indikator User Experience Aplikasi SIMPONI Mobile Universitas Multi Data Palembang Menggunakan User Experience Questionnare - Gerry Tanjungan (MDP Student Conference, 2022)
Abstract: Multi Data Palembang University during the lecture process provides several online media for students. One of the online media provided by MDP University is Simponi Mobile. The importance of the SIMPONI Mobile application for users, needs further analysis in user experience satisfaction to find out whether the application needs improvement or has met the needs of its users, using the User Experience Questionnaire (UEQ) method In collecting data by distributing questionnaires to users of the SIMPONI mobile application, namely college student. The design of the questionnaire in the form of a number of questions as indicators of research variables with the aim and results to be achieved is that SIMPONI mobile can be better for users of the SIMPONI mobile application from the 6 UEQ scales, namely attractiveness, perpicuity, efficiency, dependability, stimulation, and novelty. Abstrak: Universitas Multi Data Palembang selama proses perkuliahan menyediakan beberapa media online untuk mahasiswa.. Salah satu media online yang disediakan oleh MDP University adalah SIMPONI Mobile. Pentingnya aplikasi SIMPONI Mobile bagi pengguna, butuh di analisis lebih lanjut dalam kepuasan pengalaman pengguna agar mengetahui apakah aplikasi tersebut perlu adanya peningkatan atau sudah memenuhi kebutuhan para penggunanya, dengan menggunakan metode User Experience Questionnaire (UEQ). Dalam pengumpulan data dengan cara menyebarkan kuesionar kepada pengguna aplikasi SIMPONI mobile, yaitu mahasiswa. Rancangan kuesioner berupa sejumlah pertanyaan sebagai indikator variabel penelitian dengan tujuan dan hasil yang ingin dicapai adalah SIMPONI mobile dapat menjadi yang lebih baik untuk para pengguna aplikasi SIMPONI mobile dari 6 skala UEQ, yaitu attractiveness, perpicuity, efficiency, dependability, stimulation, dan novelty.